2016
DOI: 10.1080/10401334.2015.1107490
|View full text |Cite
|
Sign up to set email alerts
|

How Comprehensively Is Evidence-Based Practice Represented in Australian Health Professional Accreditation Documents? A Systematic Audit

Abstract: Occurrence of the term evidence as it relates specifically to "evidence-based practice" ranged from 0 (pharmacy, dentistry and occupational therapy) to 8 (physiotherapy) in the accreditation documents. Overall, there were 77 occasions when terms relating to any of the 5 steps of evidence-based practice were used across all 11 accreditation documents. All 5 steps were included in the physiotherapy and psychology documents; 4 steps in medicine and optometry; 3 steps in pharmacy; 2 steps each in documents for chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The support for EBP with the use of explicit terms was generally disappointing in the CCE educational standards. These documents have the potential to act as drivers for education providers to embed EBP into practice [16]. EBP has been shown to influence educational, entry-level graduates and practitioner levels of care which in turn has improved patient outcomes [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The support for EBP with the use of explicit terms was generally disappointing in the CCE educational standards. These documents have the potential to act as drivers for education providers to embed EBP into practice [16]. EBP has been shown to influence educational, entry-level graduates and practitioner levels of care which in turn has improved patient outcomes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Educational standards adopted and monitored by educational regulatory agencies across 11 health profession bodies in Australia were compared in a recent study [16]. The authors compared the frequency of the appearance of EBP-related terms, such as the word evidence, in documents for informing educational programs of required accreditation standards of the need for EBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 An audit of Australian accreditation documents for 12 health professions (medicine, nursing, midwifery, pharmacy, physiotherapy, dentistry, psychology, occupational therapy, optometry, podiatry, osteopathy, and chiroprac-tic) was published in 2016. 14 It found that only physiotherapy and psychology fully complied with the 2005 Sicily statement on the 5-step model of training in evidencebased practice; medicine and optometry complied with 4 of the statements, pharmacy with 3, and chiropractic, osteopathy and podiatry with 2.…”
Section: Introductionmentioning
confidence: 99%
“…This change over the last decade may be due to elevated awareness of the importance of teaching evidence-based practices at the training level and increased emphasis on their use by licencing bodies in developed countries (Mcevoy et al 2016). However, the developing countries of India, Ghana and Thailand still report excessive use of passive treatments.…”
Section: Treatment Methodsmentioning
confidence: 99%